Unreal Engine: Motion Graphics Techniques. - Pagano, Scott (linkedin.com, 2016)
Discover helpful methods and ways to use UE4. Explore asset design, preparation, and transfer. Learn about blend shapes, rigs, rendering, using FBX and Alembic files, and more.